2021
DOI: 10.3390/nano11071825
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Pt-Based Alloy Nanoparticles Assisted by Molybdenum Hexacarbonyl

Abstract: We report on an optimized, scalable solution-phase synthetic procedure for the fabrication of fine-tuned monodisperse nanostructures (Pt(NiCo), PtNi and PtCo). The influence of different solute metal precursors and surfactants on the morphological evolution of homogeneous alloy nanoparticles (NPs) has been investigated. Molybdenum hexacarbonyl (Mo(CO)6) was used as the reductant. We demonstrate that this solution-based strategy results in uniform-sized NPs, the morphology of which can be manipulated by appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…Pt(NiCo)-Mo, PtNi-Mo, and PtCo-Mo NPs were prepared using our synthetic procedure described elsewhere. 35 Electrochemical measurements show that these Pt-solute-Mo nanoalloys, immobilized on a carbon black support material, display enhanced electrocatalytic performances in the HER, ORR, and MOR and are ultra-durable in terms of CO ads poisoning tolerance in an acidic electrolyte when compared with a commercially available Pt/C electrocatalyst. Stability measurements showed that the initially outstanding catalytic activities degraded in the ORR and MOR as a function of extended electrochemical cycling to 8k cycles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pt(NiCo)-Mo, PtNi-Mo, and PtCo-Mo NPs were prepared using our synthetic procedure described elsewhere. 35 Electrochemical measurements show that these Pt-solute-Mo nanoalloys, immobilized on a carbon black support material, display enhanced electrocatalytic performances in the HER, ORR, and MOR and are ultra-durable in terms of CO ads poisoning tolerance in an acidic electrolyte when compared with a commercially available Pt/C electrocatalyst. Stability measurements showed that the initially outstanding catalytic activities degraded in the ORR and MOR as a function of extended electrochemical cycling to 8k cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Alloy NP structures of Pt(NiCo)-Mo, PtNi-Mo, and PtCo-Mo were solution-derived by co-reducing precursors platinum acetylacetonate (Pt(acac) 2 , 97%), nickel(II) acetate tetrahydrate (Ni(Ac) 2 , 95%), and/or cobalt(II) acetate tetrahydrate (Co(Ac) 2 , ≥99%) with molybdenum hexacarbonyl (Mo(CO) 6 , 98%) in the presence of amine surfactants oleylamine (OAm, 70%) and hexadecylamine (HDA, 90%) in a high boiling point solvent benzyl ether (BE, 98%) at 240 °C for 60 min. 35 In a typical synthesis, metal precursor sources (Pt(acac) 2 (0.08 g, 0.2 mmol) + Ni(Ac) 2 (0.048 g, 0.2 mmol)), (Pt(acac) 2 (0.08 g, 0.2 mmol) + Co(Ac) 2 (0.048 g, 0.2 mmol)), or (Pt(acac) 2 (0.08 g, 0.2 mmol) + Ni(Ac) 2 (0.024 g, 0.1 mmol) + Co(Ac) 2 (0.024 g, 0.1 mmol)) were dissolved in binary surfactants OAm (20 mL) and HDA (4.4 g) using BE (25 mL) as the high boiling point solvent. The resulting metal salt−surfactant−solvent reaction mixture was heated to 150 °C for 5−10 min under vigorous magnetic stirring in a roundbottom flask.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…16 These external factors can include capping agents and mixtures thereof that selectively cap specific facets, [33][34][35][36] or temperature and precursor concentration that encourage growth in the kinetic regime. 20,37 Two theories have been developed to explain branching; atomic deposition 38 and oriented attachment. 39 In the first, atoms continuously add to high energy NP facets, with branching seen when the deposition rate exceeds that of the subsequent migration of these adatoms to lower energy facets.…”
Section: Introductionmentioning
confidence: 99%